2018
DOI: 10.1152/japplphysiol.01123.2017
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia improves behavioral and adrenal gland dysfunction induced by posttraumatic stress disorder in rats

Abstract: Nonpharmacological treatments of stress-induced disorders are promising, since they enhance endogenous stress defense systems, are free of side effects, and have few contraindications. The present study tested the hypothesis that intermittent hypoxia conditioning (IHC) ameliorates behavioral, biochemical, and morphological signs of experimental posttraumatic stress disorder (PTSD) induced in rats with a model of predator stress (10-day exposure to cat urine scent, 15 min daily followed by 14 days of stress-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 46 publications
(60 reference statements)
5
38
0
10
Order By: Relevance
“…In stressed PTSD+IHC rats, AI was decreased compared to that of PTSD rats, i.e., IHC produced significant protection from PTSD. This result confirms our earlier study [18]. In that earlier study, we performed the X-maze test to demonstrate that PTSD did not develop in the IHC rats exposed to predator stress in contrast to non-IHC rats exposed to the same stress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In stressed PTSD+IHC rats, AI was decreased compared to that of PTSD rats, i.e., IHC produced significant protection from PTSD. This result confirms our earlier study [18]. In that earlier study, we performed the X-maze test to demonstrate that PTSD did not develop in the IHC rats exposed to predator stress in contrast to non-IHC rats exposed to the same stress.…”
Section: Discussionsupporting
confidence: 90%
“…IHC preconditioning [16] and postconditioning [17] were shown to abolish development of stress-induced anxiety in the rat "stress-restress" model of PTSD. Recently we found that rats treated with IHC prior to predator stress exhibited significantly less anxiety-like behavior, a lesser drop of plasma corticosterone, and reduced structural signs of adrenal gland dystrophy, all signs characteristic of PTSD [18]. In fact, IHC exerted a robust anti-stress effect in naïve rats, as evidenced from less anxiety during an elevated X-maze test [18].…”
Section: Introductionmentioning
confidence: 96%
“…The decrease in animals AI after chronic PSS, observed two weeks after the last exposure to the stressor, is similar to this reported in our previous studies (Lazuko et al 2018;Manukhina et al 2018). Our funding on the altered 5-HT transmission in the thalamus is consistent with previous studies by other groups.…”
supporting
confidence: 92%
“…Repeated exposure of the rats to the predator scent stress (PSS) has been used in our previous studies as an animal model of post-traumatic stress disorder (PTSD). We had previously reported that repeated PSS induce long-lasting behavioral changes, such as increased anxiety index (AI), observed as late as fourteen days after the last PSS exposure (Lazuko et al 2018;Manukhina et al 2018). Repeated PSS might be a more accurate model for PTSD than the acute one, since it minimizes the effect of uncontrolled factors, such as concentration of pheromones in each individual dose of urine.…”
mentioning
confidence: 99%
“…Moreover, an activation of MAO-A expression in neurons via higher ability to receptor binding was described for glucocorticoids [10]. Interestingly, low levels of basal corticosterone [16] and low levels of cerebral MAO without distinguishing the isoforms of MAO linked to physical activity were shown in rats, three days after traumatic stress [17]. And, in more physical active offensive rats we found a reduction of anxiety, corticosteroids and glutamate as well as higher concentrations of lactate in the amygdala region compared to the hippocampal region by using our model of chronic and extensive predator stress, indicating a limbic triggered HPA activity with different oxidative processes [18].…”
Section: Mao Metabolism In Ptsdmentioning
confidence: 96%